Acoustic characterization of rehabilitated cloisters - A. P. O. Carvalho (2008)
This paper presents the results of field measurements in eight rehabilitated cloisters of old monasteries in Portugal (length: 20 to 35 m and height: 3.3 to 6.3 m) regarding their acoustic behavior to two objective parameters: RT and RASTI. The goal is to characterize the acoustic effect of the rehabilitation done on theses spaces to adapt them to new uses. All these cloisters had recently their galleries openings to the central yard closed with glass panels. Simple formulas were obtained that relate among the objective acoustic parameters and between the acoustic and architectural parameters. This paper also presents the variation on the RASTI and RT average values resulting of the rehabilitation work done on these buildings.